Allogenic Bone Tissue in Maxillary Reconstruction - A feasible Alternative - Camarini, Edevaldo Tadeu; Leite, Pablo Cornélius Comelli; Bachega, Karla; Acceturi, Eduardo (Brazilian Journal of Transplantation, 2007)
Purpose: The authors propose to demonstrate the allogenic bone grafting related to the reconstruction of the maxillary alveolar process for dental implant installation. Methods: clinical and pre and post grafting radiographic analysis were used on the maxillary sinus (sinus lifting) and after implant installation in an eight years case evolution. Results: The radiographic examination showed an appropriate bone neo formation able to receive dental implants which remained properly functional for eight years. Conclusion: due to their advantages, allograft bones can be considered a good alternative related to alveolar processes reconstruction of the maxillary for dental implant.